Perlindungan Hukum Konsumen dalam Jual Beli Akun Mobile Legends Online Menurut UU No. 11 Tahun 2008 dan UU No. 8 Tahun 1999 - Putu Budi Utama; Ratna Artha Windari; Si Ngurah Ardhya (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The informal trading of Mobile Legends: Bang Bang game accounts through social networking platforms has expanded rapidly alongside the acceleration of digital technology and the growing integration of online gaming into contemporary lifestyles, particularly among younger demographics. Game accounts characterized by high competitive rankings, exclusive virtual assets, and accumulated in-game achievements have increasingly been commodified and exchanged through social media channels such as Facebook, Instagram, and TikTok, predominantly utilizing electronic payment instruments, including digital wallets. Despite its widespread practice, this form of transaction frequently generates legal complications, most notably in relation to consumer protection. Buyers are often exposed to substantial risks, including fraudulent representations, discrepancies between promised and actual account specifications, unauthorized resale, and the revocation of account access after payment completion. This study seeks to critically examine the legal framework governing the trading of Mobile Legends accounts and to assess the extent to which consumer protection mechanisms are afforded under Law Number 11 of 2008 concerning Electronic Information and Transactions and Law Number 8 of 1999 concerning Consumer Protection. Employing a normative juridical research design, this study applies statutory and conceptual approaches supported by the analysis of primary, secondary, and tertiary legal materials. The findings indicate that consumer protection within online game account transactions remains structurally insufficient, primarily due to the absence of explicit legal recognition of digital game accounts as legally protected objects. Consequently, the study underscores the necessity of adopting progressive legal interpretation and formulating specific regulatory instruments to enhance legal certainty and ensure more effective consumer protection within the evolving landscape of digital transactions.